Impact of the COVID-19 pandemic on perceived access and quality of care in German people with parkinsonism - van Munster, Marlena; Printz, Marcel R.; Crighton, Eric; Mestre, Tiago A.; Pedrosa, David J.; , iCARE-PD Consortium (Frontiers in Public Health, 2023)
Due to the heterogeneous clinical presentation, people with Parkinsonism (PwP) develop individual health care needs as their disease progresses. However, because of limited health resources during the COVID-19 pandemic, many patients were put at risk of inadequate care. All this occurred in the context of inequitable health care provision within societies, especially for such vulnerable populations. This study aimed to investigate factors influencing satisfaction and unmet need for health care among PwP during the COVID-19 pandemic in Germany. Analyses relied on an anonymous online survey with a 49-item questionnaire. We aimed at describing access to health services before and during early stages of the pandemic. To this end, a Generalized Linear Model was used to derive significant predictors and a stepwise regression to subsummarise the main factors of perceived inadequate care. In total, 551 questionnaires showed that satisfaction for Parkinsonism-related care decreased significantly during the pandemic (p < .001). Especially, factors such as lower educational level, lower perceived expertise of healthcare providers, less confidence in remote care, difficulties in obtaining healthcare and restricted access to care prior to the pandemic but also lower densities of neurologists at residence and less ability to overcome barriers were indicative of higher odds to perceive unmet needs (p < .05). The results unveil obstacles contributing to reduced access to healthcare during the COVID-19 pandemic for PwP. These findings enable considerations for improved provision of healthcare services to PwP.